FROM THE TRADITIONAL CLASSROOM TO THE VIRTUAL CLASSROOM: A LITERATURE REVIEW ON THE EFFECTIVENESS OF DISTANCE LEARNING - Ismaul Fitroh; Heru Widoyo; Moh. Imron Rosidi (Adisam Publisher, 2026)
This study reviews the literature related to the effectiveness of distance learning (PJJ) in the context of the transition from traditional to virtual classes. The results show that the successful implementation of distance learning is largely determined by several key factors, namely adequate technological infrastructure, teacher readiness and competence in managing virtual classes, and student engagement and discipline. In addition, support from parents and a conducive home environment are proven to play an important role in supporting students' learning process. A curriculum specifically designed for distance learning is also a crucial factor to ensure optimal student interaction and engagement. By considering and optimising these factors, distance learning can be an effective and comparable alternative to traditional face-to-face learning. This study provides guidance for education practitioners in designing and implementing distance learning more efficiently and effectively.